"Only so that my daughter gets exposure to the culture": Ethnic leisure practices and intangible cultural heritage in British Indian diasporic families. Issue 3 (2nd September 2021) - Mukherjee, Utsa
Abstract : Intangible cultural heritage (ICH) as a concept has received considerable scholarly attention in recent years. However, empirical understanding of how ICH migrates, and is transmitted within diasporic communities is sparse. This paper draws upon a qualitative study with middle-class British Indian families living in and around London to unpack the ways in which ICH is enacted, interpreted, and transmitted from across generation through the construction of diasporic leisure spaces. Based on interviews with parents and children and observation of festival sites, it is argued that the leisure–ICH nexus in the diaspora materializes through two interlinked processes: "transmission of ethnic cultural capital" and "place-making." These processes draw upon and contribute to diasporic social networks. In exploring these intersections, the paper further draws attention to how the internal differentiations within diasporic communities inflect the (re)production of diasporic leisure and ICH in the context of contemporary urban multi-culture in London.